The stylistics of professional discourse - Solly, Martin (Edinburgh University Press, 2016)
The volume proposes a stylistics perspective to investigate the discourse of professional communities. It provides an overview of the evolving field of stylistics and its potential for analysing texts, then goes on to apply these theoretical and methodological tools to three specific communities: healthcare, law and education